Oscillation of solutions of the second-order linear functional-difference equations - Karpenko, O. V.; Kravets, V. I.; Stanzhitskii, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We establish conditions for the oscillation of solutions of functional difference linear equations and discrete difference linear equations of the second order in the case where the corresponding solutions of their differential analogs are oscillating on a segment.